Data encryption based on 7D complex chaotic system with cubic memristor for smart grid - Kou, Lei; Huang, Zhe; Jiang, Cuimei; Zhang, Fangfang; Ke, Wende; Wan, Junhe; Liu, Hailin; Li, Hui; Lu, Jinyan (Frontiers in Energy Research, 2022)
The information security has an irreplaceable position in the smart grid (SG). In order to avoid the malicious attack and ensure the information security, the cryptographic techniques are essential. This paper focuses on the encryption techniques to ensure the information security of SG. Firstly, an unusual 7-dimensional complex chaotic system (7D-CCS) combined with the cubic memristor is introduced. Besides its phase portraits, Lyapunov exponent, 0–1 test, complexity, and bifurcation diagram are investigated. Then, with the proposed 7D-CCS, we design a data encryption algorithm to ensure the encryption security. Finally, the data and monitoring images in SG are encrypted by the designed encryption scheme. Besides, the encryption performance is given in detailed. The experimental results show that the proposed encryption scheme has quite good encryption performance. Therefore, it can ensure the information security of SG.